Exponential mathematical law applied to cardiac dynamics for 18 hours (2023)
An exponential law was previously developed based on dynamic systems theory to be applied to cardiac dynamics in 21 hours, so it is wanted to reduce the time of evaluation to 18 hours, to further verify its diagnostic utility differentiating normal from abnormal cardiac dynamics. To do that, 250 continuous electrocardiographic records and Holters were taken, from which 50 were normal and 200 had cardiac pathologies. Then, values of the maximum and minimum heart rates and the number of beats per hour were taken to generate a pseudo-randomized sequence in 21 and 18 hours and generate attractors. Later, occupation spaces were calculated in Kp and Kg grids as well as the fractal dimension, establishing a mathematical diagnosis Finally, the sensitivity, specificity and kappa coefficient were calculated to compare the obtained values with the Gold Standard. Normal dynamics presented occupation spaces values in the Kp grid between 233 and 401, while the abnormal ones were between 43 and 198 in 18 hours. Sensitivity and specificity values of 100% were found, with a Kappa coefficient of 1. It was possible to differentiate normal from abnormal cardiac dynamics through occupation spaces in 18 hours confirming its clinical utility. © 2019 Published under licence by IOP Publishing Ltd.